SAT0041 Efficacy of abatacept versus adalimumab in patients with seropositive, erosive early ra: analysis of a randomized controlled clinical trial (AMPLE). (15th June 2017) - Fleischmann, R; Weinblatt, M; Ahmad, H; Maldonado, M; Alemao, E; Ye, J; Schiff, M
Abstract : Background: Patients (pts) who are anti-citrullinated protein antibody (ACPA) positive tend to develop more severe erosive disease than ACPA-negative pts. 1 The presence of seropositivity and erosions have been noted in EULAR treatment guidelines as poor prognostic factors to identify pts with RA who require early and aggressive clinical intervention. 2 Since the disease in pts with seropositive, erosive early RA is mostly driven by immunological features, response to RA therapy may vary based on therapeutic mechanism of action (MOA). Objectives: To investigate the efficacy of abatacept (ABA) vs adalimumab (ADA) in pts with seropositive, erosive early RA. Methods: AMPLE (NCT00929864 ) 3 was a 2-year, Phase IIIb study in which biologic-naïve pts with RA were randomized 1:1 to either SC ABA 125 mg weekly or SC ADA 40 mg biweekly, both with background MTX. This post hoc analysis of AMPLE compared clinical outcomes between treatment groups in a subpopulation of pts with specified baseline criteria: disease duration ≤6 months, RF or ACPA seropositivity and >1 radiographic erosion. Disease activity and patient-reported outcomes were evaluated at Weeks 26, 52 and 104. Endpoints were compared between ABA and ADA groups using chi-square test for categorical variables, analysis of covariance model (ANCOVA) controlling for baseline covariates and DAS28 (CRP) stratification for continuous variables. Results: Of 318 and 328 pts in the ABA and ADA groups, respectively, 38 and 45 pts had all specified baseline characteristics (Cohort 1) and 280 and 283 pts had an absence of at least 1 of the specified characteristics (Cohort 2). Overall, the baseline characteristics, including anti-cyclic citrullinated peptide titres, were well balanced between the groups, with the exception of weight. For Cohort 1, adjusted mean change (95% CI) from baseline DAS28 (CRP) with ABA vs ADA was –2.18 (–2.61, –1.75) vs –1.56 (–2.01, –1.11) at Week 26, –2.58 (–2.99, –2.17) vs –1.68 (–2.10, –1.25) at Week 52 and –2.50 (–2.97, –2.03) vs –2.0 (–2.49, –1.50) at Week 104. Similar trends of increased efficacy with ABA vs ADA were observed for changes from baseline CDAI, SDAI, HAQ-DI, pain and fatigue; no differences in radiographic progression were observed. For Cohort 2, no differences in clinical outcomes between ABA and ADA groups were observed. Given the differences in baseline weight between ABA and ADA groups in Cohort 1, sensitivity analyses that excluded pts >100 kg and adjusted for baseline weight were performed and demonstrated minimal effect of weight on treatment efficacy. Conclusions: This post hoc analysis seems to indicate a trend of increased efficacy for abatacept in pts with seropositive, erosive early RA compared with the TNF inhibitor adalimumab. Given the small sample size, additional pre-specified randomized studies are needed to compare the benefit of biologic DMARDs with different MOAs in pts with early, rapidly progressing RA. References: Combe B, et al. Ann Rheum Dis 2016 Dec 15. doi: 10.1136/annrheumdis-2016–210602. Aletaha D, et al. Arthritis Rheum 2010;62:2569–81. Weinblatt M, et al. Arthritis Rheum 2013;65:28–38. Disclosure of Interest: R. Fleischmann Grant/research support from: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Roche, sanofi-aventis, UCB, Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Pfizer, Roche, sanofi-aventis, UCB, M. Weinblatt Grant/research support from: Amgen, Bristol-Myers Squibb, Crescendo Bioscience, UCB, DxTerity, Consultant for: Amgen, Bristol-Myers Squibb, Crescendo Bioscience, UCB, AbbVie, Lilly, Pfizer, Roche, H. Ahmad Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Maldonado Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Ye Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Schiff Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, JNJ, UCB, Speakers bureau: AbbVie